2012
DOI: 10.1590/s0102-67202012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Resultados da gastrectomia D2 para o câncer gástrico: dissecção da cadeia linfática ou ressecção linfonodal múltipla?

Abstract: -Background -Eastern literature is remarkable for presenting survival rates for surgical treatment of gastric adenocarcinoma superior to those presented in western countries. Aim -To analyze the long-term result after D2 gastrectomy for gastric cancer. Methods -Two hundred seventy four underwent gastrectomy with D2 lymph node dissection as exclusive treatment. The inclusion criteria were: 1) lymph node removal according to Japanese standardized lymphatic chain dissection; 2) potentially curative surgery descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In patients with other types of cancer, such as breast or lung cancer, tumor size is still an important predictor. In gastric cancer, however, the prognostic value of tumor size remains controversial 16 , 29 . Some authors showed that tumor size can be an important factor as for aggressiveness 9 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with other types of cancer, such as breast or lung cancer, tumor size is still an important predictor. In gastric cancer, however, the prognostic value of tumor size remains controversial 16 , 29 . Some authors showed that tumor size can be an important factor as for aggressiveness 9 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…How to make the best choice among the possible treatments for EGC, including EMR/ESD [ 19 ], laparoscopic gastrectom [ 20 ]and traditionalD1 or D2 radical resection [ 21 ], remains debatable. Pre-operative LNM status will certainly be useful information when making a clinical decision.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, D2 lymphadenectomy, which allows for clearance of the nodal stations likely harboring metastatic disease and increased number of nodes for evaluation, is now internationally accepted as the standard procedure with demonstrated decreased regional recurrence and improved long-term survival for patients undergoing curative surgery (913). Thus, many guidelines (Italian Gastric Cancer Study Group, the German Gastric Carcinoma Study Group, the Brazilian Gastric Cancer Association and the Chinese Gastric Cancer Association) support D2 lymphadenectomy as the optimum extent of lymph node dissection (1416). While D2 lymph node dissection has long been advocated as the surgical standard for radical gastrectomy in Japan and South Korea by the Japanese Research Society for Gastric Cancer and Korean Gastric Cancer Association (17, 18), D2 lymphadenectomy in Western studies has until recently been associated with forbidding morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%